PENERAPAN SISTEM PEMBELAJARAN âFUN & FULL DAY SCHOOLâ UNTUK MENINGKATKAN RELIGIUSITAS PESERTA DIDIK DI SDIT AL ISLAM KUDUS - NURHAYATI, IDA (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
Education expected to increase youngsters quality in many aspects to lessen and or decrease the cause of cultural and national character problem, whilst religion, act as barrier, to decide which is good or bad, before they act. That is why the need of education combinedÂ  with religious belief to increase students religious understanding to prevent youngsters wrong doings. This study is to describe planning, implementation, evaluation, problem identification, and solution in deal with implementation problems of "fun & full day school" system to increase students religious belief in SDIT Al Islam Kudus.This is a qualitative descriptive study. Data were taken from informans, place and events, and documents. The informans are headmaster himself, teachers and students in SDIT Al Islam Kudus. Place and events of implementation of the "fun & full day school" learning process is SDIT Al Islam Kudus. Documents for data sources were photos, files, or papers related with lessons in SDIT Al Islam Kudus. According to source, the data from field observation, data from lesson plans and data collecting technique using triangulation were combination of interviews, observations and documentations.From the study, the conlusions are, 1) SDIT Al Islam Kudus has well planned their lessons by developing and managing the lessons in "fun & full day school" with teachers planning according Dick, Carey and Careys model. 2) Implementation of integrated and balanced lesson in "fun & full day school" has ran well in purpose to create religious generations 3) Evaluations in the "fun & full day school" to students increase religious belief have been using varied assesment techniques and methods. 4). Problems of "fun & full day school" system was from two sources, they are students and teachers. Â Keywords: Fun and Full day School system, students religious belief